STRATEGI PENINGKATAN KINERJA ASN MELALUI APLIKASI PENILAIAN KINERJA APARATUR (SIKERJA) DI IPDN KAMPUS KALIMANTAN BARAT - Desty Pratiwi; Silverius Tey Seran (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2018)
ABSTRACT The essence of the SIKERJA application is to improve the quality of work. Before the SIKERJA application as actually implemented, a trial period of around 6 (six) months was carried out, at the beginning of 2017, SIKERJA was officially put in place to accommodate performance achievement through the SIKERJA application has not been implemented in accordance with expectations. Therefore, strategies and steps to improve performance and application are needed to be effective and increase work output and value of application functions so that the rapid development of information technology can be maximized for the benefit of the organization in an effort to improve ASN performance. The Six indicators that will be carried ot in the implementation of a performance improvement strategy include: quality, quantity, teamwork, creativity, innovation, initiative.The results of the study explain that SIKERJA application still needs to be updated because the ASN performance data has not been accommodated. In the renewal of the application is also needed a periodic discussion to collect information and find solutions to a problem that occurs. Effective work minutes that have been set have been adjusted to the workload and job targets that must be achieved so that employees who do not achieve the working minutes are required to get strict sanctions. SIKERJA Verifiers are also expected to work optimally so that SIKERJA input can be more controlled and controlled in accordance with the prevailing corridors. The method of research with qualitative and exploratory approach is more appropriate to be used in analyzing a variety of realities that are more complete and to explore the actual informations in analyzing of the six indicators. Keywords: strategy, performance assessment, civil servants